The efficient and final causes of the spiritual power in the D. Friar Álvaro Pais’ sigth - De Souza, José Antônio De C. R. (Anales del Seminario de Historia de la Filosofía, 2008)
In this study, based in the main political works of D. Fr. Alvarus Pelagius O. Min. (c. 1270- c.1350) we analyze his conception on the origin or efficient cause of the spiritual power and, also, his thought about the finality or final cause of the mentioned power. Referring to the first topic, the Bishop of Silves wants principally refutes some Marsilius of Padua’s thesis contained in the Second Dictio of his Defensor Pacis, completely different of the theology of the catholic priesthood and their hierarchic degrees and the Peter’s Primacy. With this purpose, ad litteram, he bases, between other sources, specially, in James’ of Viterbo OSA De regimine christiano (1301). Concerning the finality of the spiritual power, on the one hand, Alvarus supports the Church’s traditional thought about this matter and, the other hand, by consequence, as member and defender of the hierocratic thought, he defends the thesis according which, in the Societas Christiana, the priests, the bishops and, principally, the Roman Pontiff hold the most important position concerning the secular rulers.